SDM DAN UMUM SEBAGAI PENDUKUNG OPERASIONAL PG REJO AGUNG BARU MADIUN - Mukhlis Ardiansyah; Nanang Cendriono (Jurnal Pijar, 2026)
The general internship program was conducted at PG Rejo Agung Baru Madiun, with a focus on the Human Resources (HR) and General Affairs Department. The purpose of this journal is to examine the implementation of the work system, work programs, and the relevance of the internship activities to the field of study, as well as to identify the obstacles encountered and the efforts undertaken to address them. The method used in preparing this journal includes direct observation, active participation in work activities, and documentation studies during the internship period. The results of the observations indicate that the work system in the HR and General Affairs Department has been implemented fairly well and in a structured manner, supported by a clear division of tasks and the application of work procedures. The work programs carried out play an important role in supporting the smooth administration of personnel management and general services. However, several constraints were still identified, such as administrative processes that have not yet been fully digitalized and limited system integration, which require more time and careful attention in their implementation. Based on these findings, improvement efforts are needed through enhancing administrative digitalization, integrating the attendance system with personnel data, and improving HR competencies. With these improvements, it is expected that the performance of the HR and General Affairs Department of PG Rejo Agung Baru Madiun will become more effective and efficient in supporting the company’s objectives. This journal is expected to provide an overview and a reference for the development of human resource management in the industrial environment.